"5th International Workshop on Software Process Simulation and Modeling (ProSim 2004)" W11L Workshop - 26th International Confe 2004
DOI: 10.1049/ic:20040440
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integration of process modeling and project planning

Abstract: Most development projects have very complex dependencies regarding the tasks to accomplish. Process models offer the chance to incorporate the knowledge of many project managers into active projects. Bridging the gap between process models and project plans by defining such models precisely seems to be beneficial. In this paper, we show the benefits and highlight some of the interesting problems of integrating process modeling and project planning. We introduce metamodeling techniques to constrain the instanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We found that the communication difficulties between the subgroups were largely caused by the discrepancies of the adopted PPMs between the subgroups in Sri Lanka and Japan. PPM (project process model) is defined as the abstract representations of a product development process and how tasks are aligned and accomplished during the project (Gnatz, Deubler, Meisinger, & Rausch, 2004). PPMs are based on the members' previous experiences and/or some contagion effects at the local working environment due to daily in-person interactions and cultural influences.…”
Section: Description Example Quotes Language Mediators As Communicati...mentioning
confidence: 99%
“…We found that the communication difficulties between the subgroups were largely caused by the discrepancies of the adopted PPMs between the subgroups in Sri Lanka and Japan. PPM (project process model) is defined as the abstract representations of a product development process and how tasks are aligned and accomplished during the project (Gnatz, Deubler, Meisinger, & Rausch, 2004). PPMs are based on the members' previous experiences and/or some contagion effects at the local working environment due to daily in-person interactions and cultural influences.…”
Section: Description Example Quotes Language Mediators As Communicati...mentioning
confidence: 99%
“…At times, the application of such models is considered less important by project actors, for example, a model could be applied at the early stage of a project, and then intentionally or unintentionally ignored at the following stages. 31 To improve the usability of process management models, researchers have shown that it is necessary to reduce human intervention. Hence, computer-aided technologies need to be integrated.…”
Section: Related Workmentioning
confidence: 99%
“…The second scenario occurs when the process to formalize is an extension/adaptation of an existing one, that may be already formalized or not. Such a defined and therefore repeatable process offers the chance to incorporate the knowledge and the lessons learned of many seasoned project managers into active projects [4]. In this case, one may apply reuse techniques (based on mappings) as those existing in SPEM.…”
Section: A Stage 1: Formalize the Processmentioning
confidence: 99%